Swelling and Mechanical Properties of Polyelectrolyte Hydrogels: Effect of Crosslinker - Monjur, Asima; Ahmed, Saika; Susan, Md Abu Bin Hasan (Dhaka University Journal of Science, 2025)
One of the fundamental approaches in controlling the swelling and mechanical characteristics of hydrogels involves modification of polymer network system through crosslinking. In this study, the crosslinking density in poly(acrylic acid) (PAA) hydrogels has been varied with a goal to investigate how certain swelling parameters and mechanical properties of polyelectrolyte hydrogels get influenced by their network structure; in specific, the stiffness of the bulk network of the hydrogel. PAA hydrogels were successfully prepared via UV polymerization using variable concentration of the crosslinker (0.02, 0.04, and 0.06 mol% with respect to monomer), N,N’-methylenebisacrylamide. After equilibrium swelling of the synthesized gels in water, all the polyelectrolyte hydrogels showed significant water absorption with their equilibrium water content in the range of 83-90%. The mechanical parameters of the prepared PAA gels were then determined from tensile tests. The PAA hydrogel synthesized from the highest crosslinker content was found to exhibit the highest elastic modulus of about 34 kPa. The extent of stress introduced inside the bulk hydrogel during crosslinking was also evident from their thermogravimetric studies, which showed a distinct pattern. The significant capacity for both water absorption and extensibility of the synthesized PAA hydrogels gives an indication of their potential in stress-bearing applications, especially biological ones. Dhaka Univ. J. Sci. 73(1): 77-86, 2025 (January)